STRATEGI GURU DALAM PENINGKATAN KEMAMPUAN BACA Al-QUR’AN SISWA DI MA AT-TAUFIQ GROGOL DIWEK JOMBANG - Desy Naelasari; Nia Lutfi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
Reading the Qur'an is a basic ability that must be possessed by humans, because the process of learning Islam itself is closely related to the arguments and sources taken from the Qur'an. Allah's mercy towards humans is that He not only gives them clean qualities that can guide and guide them towards goodness, but also from time to time He sends a messenger to mankind with a book from Allah and orders them to worship only Allah. only, giving glad tidings and giving warnings. The aims of this research are 1). To describe the Strategy of Qiroatul Quran Teachers in Improving Students' Quran Reading Ability at MA at-Taufiq Grogol Diwek Jombang. 2). To describe Students' Quran Reading Ability at MA At-Taufiq Grogol Diwek Jombang. 3). To describe the supporting and inhibiting factors of Qiroatul Quran Teachers in Improving Students' Quran Reading Ability at MA at-Taufiq Grogol Diwek Jombang. The method used in this research is a descriptive qualitative research method with a field research approach. The research design used in this study is a qualitative descriptive design. With in-depth interview data collection techniques, observation, documentation and qualitative descriptive data analysis techniques. Based on the results of research conducted by researchers to answer the focus of the research above, it can be concluded as follows: Strategies in Improving Students' Quran Reading Ability, among others: 1). The teacher's ability to open lessons. 2). The ability of teachers to carry out the core of learning. 3). The ability of teachers in assessment and evaluation. 4). The teacher's ability to close the lesson. The factor that affects the students' ability to read the Koran at MA At-Taufiq itself is from the madrasa environment. The inhibiting factor experienced is the lack of awareness of the importance of learning the koran.